2000
DOI: 10.2337/diacare.23.9.1389
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E supplementation restores glutathione and malondialdehyde to normal concentrations in erythrocytes of type 1 diabetic children.

Abstract: OBJECTIVE -This study examined the relationship between cellular glutathione and vitamin E concentrations and the effect of vitamin E (␣-tocopherol) supplementation on glutathione and lipid peroxidation product concentrations in the erythrocytes of type 1 diabetic patients.RESEARCH DESIGN AND METHODS -We obtained written informed consent to participate in this study from diabetic patients (n = 29) and their age-matched nondiabetic siblings (n = 21) according to the guidelines of the Institutional Review Board … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(70 citation statements)
references
References 54 publications
(64 reference statements)
2
66
0
Order By: Relevance
“…The rats that were fed with grass-fed beef were characterized by a higher intake of α-tocopherol with the diet and, simultaneously, by a lower concentration of TBARS assayed in their plasma and liver. A relationship between α-tocopherol intake and lipid peroxidation has also observed by other authors (Jain et al, 2000;De Cabo et al 2006).…”
Section: Indicessupporting
confidence: 80%
See 1 more Smart Citation
“…The rats that were fed with grass-fed beef were characterized by a higher intake of α-tocopherol with the diet and, simultaneously, by a lower concentration of TBARS assayed in their plasma and liver. A relationship between α-tocopherol intake and lipid peroxidation has also observed by other authors (Jain et al, 2000;De Cabo et al 2006).…”
Section: Indicessupporting
confidence: 80%
“…Activation of GPx in the serum of the rats that were fed the grass-fed meat may result from the availability of glutathione or selenium in the body, but also of other redox-related molecules that cooperate with glutathione (Miyamoto et al, 2003). According to Jain et al (2000), vitamin E may restore the glutathione concentration to typical values in human erythrocytes, which may explain our results and underscore that the activity of antioxidant enzymes is related to the availability of exogenous antioxidants in the organism.…”
Section: Indicesmentioning
confidence: 56%
“…Thus, glucocorticoids may exert different tissue-specific effects. With regards to relevance to human situation, lower levels of GSH in the erythrocytes of diabetic patients and increased susceptibility to oxidative stress of these cells have been reported (Yoshida et al, 1995;Jain et al, 2000). Recently, Kim et al confirmed the effect of insulin on GSH levels and GCLC expression in rat hepatocytes and found that of the signaling pathways activated by insulin, PI3K/Akt/p70S6K are involved in mediating the effect while ERK, JNK and p38 MAPK are not (Kim et al, 2004).…”
Section: Transcriptional Regulation Of Gclcmentioning
confidence: 60%
“…This extent is dependent on cell volume, surface area, and functional integrity of cell membranes. Since it can be followed by changes in absorbance at 540 nm, the EOF test was frequently applied to the diagnosis of hemolytic diseases and oxidant alterations leading to destruction of erythrocytes [1,2,3]. For example, road transportation to slaughterhouses associated to heat stress had been demonstrated to cause increase of hemolysis in pig [3], goat [4] and camel [5].…”
Section: Introductionmentioning
confidence: 99%